PERDA: SOLUSI ALTERNATIF TERHADAP PRO DAN KONTRA UNDANG-UNDANG PORNOGRAFI: (Analisis Kritis Keamanan Negara Ditinjau dari Wawasan Nusantara) - Eko Heriyanto (Jurnal CULTURE (Culture, Language, and Literature Review), 2019)
Moral issues and crime are the main issues exhaled to support the passage of the Pornography Law. On the other hand, saving the young generation from the dangers of pornography and porno-action as the next generation of the nation’s struggle and moral decadence of the Indonesian population are among the reasons to legalize the Pornography Law. While the issues of pluralism, freedom, art and culture are often used to reject the Pornography Law. The purpose of this research is to know in general the reaction/ action of the public to the pornography and its implications, to provide solutions to the controversy of the Pornography Law itself. This research used descriptive qualitative based on a literature review which is complemented by questionnaire and expert interviews. The results of the study are since it was proposed to become a law, the Pornography Law still reaps many pros and cons in the life of the nation and state, disintegration of the nation will occur if the pros and cons of the Pornography Law continue, and a compatible local law (regarding to the community) is an alternative solution to the pros and cons for resolving the Pornography Law so far.